Performance and Progress in Information and Communication Technology in Banking Production - Asma Bouthour (Communications of International Proceedings, 2021)
This article examines the impact of information and communication technologies (ICT) on the Tunisian banking performance. The first part of this paper is devoted to the literature relating to ICT and banking research, highlighting the significance of ICT to firms and particularly to banks. The second part explores the effectiveness of investing in ICT in banking. Therefore, an empirical study has been carried out using the DEA method. Our sample is constituted of the banks of Tunisian deposits and the data was collected through the balances and the states of results of the APBT.
Keywords: ICT; banking performance; DEA method.